Extracellular Vesicles: Opportunities and Challenges for the Treatment of Renal Diseases - Tang, Tao-Tao; Lv, Lin-Li; Lan, Hui-Yao; Liu, Bi-Cheng (Frontiers in Physiology, 2019)
Extracellular vesicles (EVs) are lipid-based membrane-bound particles secreted by virtually all types of cells under both physiological and pathological conditions. Given their unique biological and pharmacological properties, EVs have spurred a renewed interest in their utility for therapeutics. Herein, efforts are made to give a comprehensive overview on the recent advances of EV-based therapy in renal diseases. The fact that EVs are implicated in various renal diseases provides us with new therapeutic modalities by eliminating these pathogenic entities. Strategies that target EVs to inhibit their production, release, and uptake will be discussed. Further, EVs-derived predominantly from stem cells can stimulate tissue repair and ameliorate renal injury via transferring proteins and nucleic acids to injured cells. Such EVs can be exploited as agents in renal regenerative medicine. Finally, we will focus on the specific application of EVs as a novel drug delivery system and highlight the challenges of EVs-based therapies for renal diseases.